Process Developments in the Cobalt Purification Circuit at Chambishi RLE Cobalt Plant of ZCCM, Zambia - A. S. Rao (The Minerals, Metals and Materials Society, 1993)
In the original roast-leach-electrowin (RLE) circuit at the Chambishi Cobalt Plant, commissioned in 1978, the separation of nickel and zinc from cobalt in aqueous streams was achieved by successive stages of precipitation using lime. However, this technique was not able to meet the increasingly stringent metal quality requirements of customers whilst maintaining acceptable process recoveries. Intensive process development work was carried out and, in July 1988, an ion exchange circuit for nickel removal was commissioned using DOW XFS 4195 resin and for the first time Z.C.C.M. produced high purity cobalt metal containing less than 0.10% nickel. Following further work, a solvent extraction circuit for zinc removal, using DZEHPA, was commissioned in February 1991 in order to enhance cobalt recovery by reducing co-precipitated cobalt losses. This paper outlines the process development, design, commissioning and subsequent operation of these nickel ion exchange and zinc solvent extraction circuits.